FAKTOR-FAKTOR YANG MENGHAMBAT PENDIDIKAN KARAKTER ANAK BURUH TANI DIKABUPATEN PONOROGO - Eri Yusnita Arvianti; Asnah Asnah; Anung Nugroho Prasetyo (BUANA SAINS, 2017)
Character education is an education that teaches about the values of human behavior associated with the Almighty God, human beings, the environment, and nationality were manifest in mind attitudes, feelings, words, and actions based on religious norms, legal norms, manners, culture, and customs. This study aims to determine the obstacles of character education and the influences of character education to children in the family farm laborers to consistency in the agricultural sector. This research was conducted in the Sukosari Village and Mojorejo Village in Ponorogo Districit from April until November 2016. The approach used in this research is quantitative and qualitative approaches. The results showed that the obstacle of parents in teaching children of farming is capital in an attempt to develop farming. Furthermore, the results of multiple regression analysis is the regression equation Y = 1.733 + 0.785X1 - 0.208X2 + 0.622X3 + ε. Hypothesis testing simultaneously explains that awareness of children, the child's feelings and actions in character education of children by parents significantly affect the consistency of child farm workers to pursue agriculture. Partial test showed awareness of children and children's actions significantly influence interest in farming in Ponorogo, while feeling effect is not significant..